Potensi Keberagamaan Masyarakat Kudus: Upaya Memperkuat Ideologi Pancasila Melalui Local Wisdom - Adlina, Atika Ulfia (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
The religious community in Indonesia need to be empowered to improve the religiosity of it quality. This religious community empowerment to maintain unity and harmony between religious livings in Indonesia. Increasing the religiosity will strengthen the Pancasila ideology of as the culture of the nation so that the massive impact of globalization reduced. The impact of globalization like changing ways of live, lifestyle, identity crisis that could trigger the morality degradation. This type of research is a qualitative descriptive study. The results of this study show that the religious community is an important potential for empowered in the framework of strengthening ideology of Pancasila. The religious community empowerment can be done via religious attributes and local wisdom.